Sport for Social Change and Development: Sustaining Transnational Partnerships and Adapting International Curriculums to Local Contexts in Rwanda. Issue 15 (12th October 2016) - Collison, Holly; Darnell, Simon; Giulianotti, Richard; Howe, P. David
Abstract: Local Non-Governmental Organisations and sports organizations have been recognized as important and well positioned strategic implementing bodies by the 'Sport for Development and Peace' (SDP) sector. Whilst they may be experienced and knowledgeable of the historical and local sociocultural landscape, many seek to form transnational partnerships, for the purpose of expanding their capacity, sustainability, and expertise. Rwanda's history of genocide frames much of its development objectives, and sport has been an integral method for implementing programmes that speak to social impact and reconciliation aims. This paper examines a transnational partnership active in Rwanda, that uses football as a tool to achieve its shared development goals. We conducted ethnographic fieldwork in Rwanda, by volunteering with the organizations as they delivered SDP programmes across the country. In doing so we were able to deconstruct the management and intricacies of this partnership and contextualize the important negotiations, management and style of approach when tackling difficult issues. This paper contributes to both expanding our knowledge of transnational partnerships and provides unique commentary that aligns the complexities of engaging with local populations in post-genocide Rwanda with 'Sport for Social Development' programming.